2021
DOI: 10.1007/s11325-021-02355-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel intraoral neuromuscular stimulation device for treating sleep-disordered breathing

Abstract: Purpose To ascertain the usefulness of a novel intraoral neuromuscular stimulation device in treating patients with primary snoring and mild obstructive sleep apnoea (OSA). This device uses daytime awake neuromuscular electrical stimulation (NMES) as an application to induce toning of the tongue muscles. Methods A prospective cohort study of 70 patients with sleep-disordered breathing was conducted. Objective snoring and respiratory parameters were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
(26 reference statements)
1
15
0
6
Order By: Relevance
“…Bipolar biphasic current was delivered with predetermined stimulation and rest periods, migrating between three low frequencies (0 to 20 Hz). The intensity of therapy (maximum of 15 mV) was controlled by the patient and they were advised to use the maximal tolerable intensity without discomfort [23]. The smartphone app was used to start and stop the device which was set to 20 min therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bipolar biphasic current was delivered with predetermined stimulation and rest periods, migrating between three low frequencies (0 to 20 Hz). The intensity of therapy (maximum of 15 mV) was controlled by the patient and they were advised to use the maximal tolerable intensity without discomfort [23]. The smartphone app was used to start and stop the device which was set to 20 min therapy.…”
Section: Methodsmentioning
confidence: 99%
“…This clinical trial was designed to expand the clinical findings of a previous study that was published recently that demonstrated a notable improvement in simple snorers and patients with mild OSA [23]. The aim of this multicenter trial was to substantiate both objective and subjective outcomes of the transoral NMES in a larger cohort, evaluate change in sleep study parameters, evaluate tolerability, and observe outcomes related sleep quality and daytime somnolence.…”
Section: Introductionmentioning
confidence: 99%
“…In a double-blind, randomised and placebo-controlled study of 67 patients, using 20 min of stimulation over 8 weeks, snoring, but not the AHI, improved with intervention [ 155 ]. In addition, the method was tested in two separate reports of the same registered clinical trial, firstly, in 70 patients [ 156 ], and secondly in 125 patients [ 157 ] with snoring and mild OSA for 20 min (once daily) over a 6-week period. It was confirmed that snoring improved [ 156 ] while there was a modest improvement in the AHI in a subgroup [ 156 ].…”
Section: Upper Airway Muscle Activitymentioning
confidence: 99%
“…Die folgende prospektive multizentrische Studie [37], deren 115 Patienten zu 56 % aus Betroffenen mit leichtgradiger OSA und zu 44 % aus Schnarchern mit einem AHI < 5/h bestand, zeigte ebenfalls wieder einen signifikanten Anstieg der schlafbezogenen Lebensqualität in beiden Gruppen: Die unter Therapie befindlichen Schnarchern verringerten den PSQI von 7,2 auf 5,8 Punkte (p < 0,001) und die Bettpartner von 6,9 auf 5,9 (p < 0,02). Analog zur vorherigen Arbeit [36] war auch hier die Tagesschläfrigkeit im ESS beim Schnarcher (8,4 auf 5,8 Punkte, p < 0,01) klar gebessert, während die Veränderung beim Bettpartner keine statistische Relevanz erreichte (6,2 auf 5,7 Punkte, p = 0,22). Ein hoher ESS-Ausgangswert korrelierte gut mit einem Therapieansprechen hinsichtlich der objektivierbaren Laustärke des Schnarchens.…”
Section: Enorales Stimulationstraining Bei Schnarchen Und Leichtgradi...unclassified
“…Dabei war die Trainingscompliance mit durchschnittlich 83% 37 bzw. 83,3% 36 hoch, wobei die Spanne für letztere Kohorte mit 59,5 bis 95,2% angegeben wird.…”
Section: Therapienutzungunclassified